Comparison of propolis to silver sulfadiazine on healing of skin wounds in rabbits - Eroksuz, Y.; Canpolat, I. (My University, 2009)
The present study showed that popolis has higher healing performance on experimental full thickness wounds in rabbits compared to silver sulphadiazine and bepanthane cream.
Keywords: Oryctolagus cuniculus